A comparative study of quality of health care services of public and private hospitals in Ghana - Adongo, Awinaba Amoah; Azumah, Francess Dufie; Nachinaab, John Onzaberigu (Journal of public health, 2022)
Aim The standard of health care service is very important to the development of every nation as indicated in the Millennium Sustainable Development Goals. There are already a growing number of reports in developing countries on the quality of health care. Nevertheless, there is scant literature in Ghana regarding the quality of health care provided by private and public health care providers. This study sought to assess and compare the quality of health care services rendered by public and private hospitals in the metropolitan cities of Ghana. Subject and Methods The study target population was patients using the selected health care facilities involved in this study. This study followed quantitative methods using a social survey designed questionnaire to obtain data from 255 hospital participants receiving care. Results The findings revealed that in contrast with the public hospitals, private hospitals offered patients a higher quality of health care services. There was no difference in meaning in terms of consistency; however, the biggest explanation was that private hospitals aimed at increasing profits and tried to attract customers to retain them as compared to public hospitals that offered basic social services to an enormous number of patients. Conclusion The study concluded that better health care services are provided by private hospitals. It was recommended that public health care providers should improve upon their quality health care services as more people visit the public health care centres due to their low health care cost.